Peningkatan Profitabilitas Melalui Hubungan Perputaran Piutang dan Perputaran Aktiva Tetap PT. Gudang Garam Tbk Periode 2010-2019 - Fajriah, Yana; Jumady, Edy (JURNAL ADMINISTRASI BISNIS (JAB), 2021)
His study aims: (1) To test and analyze the effect of accounts receivable turnover on profitability at PT. Gudang Garam, Tbk. (2) To test and analyze the effect of fixed asset turnover on profitability at PT. Gudang Garam, Tbk. (3) To test and analyze the effect of accounts receivable turnover and fixed assets turnover on profitability at PT. Gudang Garam, Tbk. The population in this study is the entire financial report data of PT. Gudang Garam Tbk and its components registered in the Stiem Bongaya Investment Gallery, for eight years from 2010 to 2019. The sample of this research is monthly financial reports from 2010 - 2019. The analysis tool used is Multiple Linear Regression. He researches results obtained (1) Accounts receivable turnover has a positive and significant effect on profitability (return on assets). (2) Fixed Asset Turnover has a negative and significant effect on profitability (return on assets). (3) Accounts Receivable Turnover and Fixed Asset Turnover have a positive and significant effect on profitability (return on assets).